Drift correction in ptychographic diffractive imaging - Zeitz, Mike; Senkbeil, Tobias; Gorniak, Thomas; Rosenhahn, Axel (Ultramicroscopy, 2013)
X-ray ptychography is a rapidly developing phase retrieval technique that combines the experimental advantages of coherent diffractive imaging with the possibility to image extended specimens. Data collection requires imaging at several scan points with high positional accuracy, which implies susceptibility to mechanical drift. This is a well-known problem in ptychographic scans, which can reduce reconstruction quality and limit the achievable resolution. Using a simple model for positional drift, we show that a set of corrected positions can be found systematically, leading to strong improvements in the reconstruction of a Siemens star dataset severely affected by drift.
Available online 23 November 2012
Gesehen am 05.11.2018